Analisis Yuridis terhadap Produk Hukum Pemerintah Daerah dalam Perspektif Prinsip Otonomi Daerah - Muh. Amin; Jamaluddin Jamaluddin (AHKAM, 2025)
The principle of regional autonomy, as guaranteed by Law Number 23 of 2014, continues to face significant challenges in its implementation, particularly concerning regulatory disharmony and the weak substantive quality of local legal instruments. This study aims to juridically analyze local government legal products through the lens of the regional autonomy principle. Employing a normative juridical approach, the study examines statutory regulations, legal doctrines, and scholarly literature to evaluate the formulation process, effectiveness, and normative barriers of local regulations. Data were collected through legal document analysis and case studies and analyzed using a qualitative-descriptive method. The findings identify three core issues: (1) inadequate vertical and horizontal harmonization between local and central regulations; (2) limited institutional capacity and human resources in the drafting and implementation of local regulations; and (3) insufficient public participation in the legislative process. These findings indicate that the implementation of regional autonomy in Indonesia remains predominantly administrative rather than substantive. Theoretically, this study proposes an integrative evaluative framework combining the principles of the rule of law, legal autonomy, and good local governance to assess the quality of local legal substance. Key recommendations include strengthening local legislative drafting institutions, enhancing participatory mechanisms, and improving central–local policy harmonization to realize a democratic, effective, and equitable regional autonomy. This study contributes conceptually to the development of the relationship between national and local law within the framework of a unitary state.